BILATERAL SIMULTANEOUS LOWER MOTOR NEURON FACIAL NERVE PALSY DUE TO GUILLAIN-BARRE SYNDROME - Manzoor, Fiza; Ayaz, Saeed Bin; Anjum, Naveed (Journal of Postgraduate Medical Institute, 2019)
Bilateral facial nerve palsy (FNP) is a rare, diagnostically perplexing clinical presentation. While idiopathic Bell's palsy is the most frequent etiology of unilateral FNP, multiple etiologies have been implicated in facial diplegia including infectious, neurologic, neoplastic, traumatic or metabolic causes. We report here, a 64-years-old male, who presented with simultaneous bilateral FNP that was attributed to Guillain-Barre syndrome. He made a noticeable recovery after conservative management.